Digital Communication & Socialization Using Media Video Content During Pandemic - Valentina, Anny; Chrissandy, Ruby; Jesslyn, Brigitta; Setyanto, Yugih (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
A continuation research about the media used by human to communicate during PSBB period. This content of this research is about type of creative contents that can be used on social media. From the previous research, it was found that, in order to survive during pandemic and to live their daily lives, human need socializing and entertainment. Those are two important things for them. The purpose of this research is to find out types of media and digital content that are not only interesting to the respondent but also effective in conveying the communication message and can be utilize as a socialization platform. The concept of